Economic Analysis of Urban Phase-level Distributed Phase-change Heat Storage Stations. (February 2019) - Li, Jun; Feng, Lun; Zhong, Shengyuan; Guo, Tiantong; Chen, Guibing
Abstract: The operation mode of "fixing heat based on power" in the heating season of "Three North" areas in China is one of the essential reasons for the phenomenon of abandoning wind power. It is an effective way to increase the rate of wind power consumption by heating through the electric heating and accumulation of heat to remove the abandoned wind power. In particular, the heat storage station built with the combination of distributed heat storage and phase change heat storage can give full play to the advantages of flexible matching, high heat storage efficiency and rapid response. This article takes this as a starting point and optimizes the annual heating gains of the distributed phase-change heat storage station. Under the conditions of thermal storage constraints, heating constraints, and combined heat supply constraints, a case study of a distributed phase-change heat storage station based on the city's functional area classification was conducted. The results show that the thermal load characteristics of the region have a significant impact on the annual return of heating period. According to the law of marginal benefit, a higher return on investment can be obtained when the heat load corresponding to the selected capacity is in the high proportion ratio range.